2016
DOI: 10.1177/0956797616649604
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve Adolescent Stress Responses

Abstract: This research integrated implicit theories and the biopsychosocial (BPS) model of challenge and threat, hypothesizing that adolescents would be more likely to conclude that they have the resources to meet the demands of an evaluative social situation when they were taught a belief that people have the potential to change their socially-relevant traits. Study 1 (N=60) randomly assigned high school adolescents to an incremental theory of personality or control condition, and then administered a standardized soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 60 publications
1
73
0
1
Order By: Relevance
“…Situation-specific stress appraisals do not operate in psychological isolation but occur within the backdrop of general belief systems (see Crum, Salovey, & Achor, 2013;Yeager, Lee, & Jamieson, 2016). The current research posits that individuals are likely to appraise intellectually demanding situations as more threatening when they believe that intelligence is fixed and cannot be developed-that is, when they hold more of an entity theory of intelligence (Blackwell et al, 2007;Dweck et al, 1995).…”
Section: Implicit Theories Of Intelligencementioning
confidence: 83%
See 2 more Smart Citations
“…Situation-specific stress appraisals do not operate in psychological isolation but occur within the backdrop of general belief systems (see Crum, Salovey, & Achor, 2013;Yeager, Lee, & Jamieson, 2016). The current research posits that individuals are likely to appraise intellectually demanding situations as more threatening when they believe that intelligence is fixed and cannot be developed-that is, when they hold more of an entity theory of intelligence (Blackwell et al, 2007;Dweck et al, 1995).…”
Section: Implicit Theories Of Intelligencementioning
confidence: 83%
“…Different analyses using the School 1 data set were reported previously in a randomized trial (Yeager, Lee, et al, 2016) and were posted online (osf.io/9ack7); data from School 2 have not yet been published. Using the School 1 data set, Yeager, Lee, et al (2016) examined the effects of a treatment teaching an incremental theory of personality-the idea that people's personalities and social traits can change-on students' coping with daily social stressors. The incremental theory of personality treatment was orthogonal to the present study for three reasons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In experiments in high schools, adolescents who received the incremental theory intervention coped with the social difficulties of moving to high school more productively than students who received a parallel control exercise. Treated adolescents reported less overall stress and earned higher grades during freshman year of high school, which can be a difficult time socially (23,33). In another study, entering ninth-graders who took part in the incremental theory intervention showed 40% fewer depressive symptoms 8-9 months after the intervention, and the effect was more prominent for those who started the year ascribing to an entity theory of personality (34,35).…”
Section: Changing Implicit Theories Through Psychological Interventionmentioning
confidence: 99%
“…Belief in an entity theory predicts more of a threat appraisal to stressors-that is, it calls into question whether fixed traits are up to the task of social success. In two studies (23), an incremental theory of personality created less of a threat appraisal and more of a challenge appraisal, both in response to a stressor (having to give a speech to upperclass students about what makes someone popular) and to typical events in high school (as reported in a daily diary).…”
Section: Appraisalmentioning
confidence: 99%